1997
DOI: 10.1002/(sici)1097-0223(199701)17:1<51::aid-pd42>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Facial Malformations

Abstract: In a prospective study, 5407 pregnant women were screened by ultrasound to detect malformations of the fetal face. Of a total of 11 facial anomalies, eight were detected by prenatal ultrasound (72 per cent). Three pregnancies were terminated because of associated developmental abnormalities or aneuploidy. In all of them, the facial malformations were correctly diagnosed. When associated with other developmental abnormalities, facial malformations were picked up at a rate of 100 per cent. Isolated facial malfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Of 21 low‐risk population studies (Table 1), all were cohort studies, seven8–14 being retrospective and 1415–28 being prospective. The retrospective cohort studies reported a large variety in the diagnostic accuracy of 2D ultrasound, with detection rates ranging from 0%11 to 70%13 for prenatal detection of all types of cleft, 33%10 to 88%9 for prenatal detection of CL ± P and 0%8, 10, 12, 13 to 22%9 for detection of CP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 21 low‐risk population studies (Table 1), all were cohort studies, seven8–14 being retrospective and 1415–28 being prospective. The retrospective cohort studies reported a large variety in the diagnostic accuracy of 2D ultrasound, with detection rates ranging from 0%11 to 70%13 for prenatal detection of all types of cleft, 33%10 to 88%9 for prenatal detection of CL ± P and 0%8, 10, 12, 13 to 22%9 for detection of CP.…”
Section: Resultsmentioning
confidence: 99%
“…In prospective cohort studies, detection ranged from 9%17 to 73%23 for prenatal detection of all types of cleft, 9%21 to 100%26 for prenatal detection of CL ± P and 0%17, 22, 24, 28 to 7%16 for detection of CP. In several studies, all prenatal diagnosis of CL ± P was confirmed following delivery or postmortem, indicating no false‐positive diagnoses9, 10, 13, 15, 18, 19, 23, 26, 27 or high specificity when there was complete follow‐up of all negative ultrasound diagnosis21, 22, 24.…”
Section: Resultsmentioning
confidence: 99%
“…, Hafner et al (13) ; Jeffrey et al (14) ; Main et al (15) ; Reisner et al (16) ; Vergani et al (17) ; Puopolo et al (18) ; Renner et al (19) , as described in The study by Jeffrey et al (14) of a prospective nature showed an incidence of sepsis of 0.2/1000 births for those patients who followed the universal screening protocol and of 1.4/1000 births for the risk factors based screening group. Regarding the retrospective cohort studies included in Figure 2, the incidence of each study were: Gibbs et al The methodology of this Systematic Review and Meta-analysis rigorously followed the recommendations of the Cochrane and the STROBE, the entire process was performed by two independent reviewers, the search strategy was broad, there was no language restriction, and the studies included were evaluated regarding their methodological content.…”
Section: Resultsmentioning
confidence: 98%
“…In summary, some isolated prenatal sonographic findings, such as facial clefts and profile abnormalities, are not necessarily indicative of aneuploidy; whereas, multiple facial abnormalities increase the likelihood of a trisomic condition (Nicolaides et al, 1992;Nicolaides et al, 1993b;Nyberg et al, 1993;Lehman et al, 1995;Hill, 1996;Hafner et al, 1997;Shields et al, 1998;Bergé et al, 2001). A detailed facial scan therefore improves the detection of a trisomy.…”
Section: Abnormal Profile/micrognathiamentioning
confidence: 99%